Fundamental of Entrepreneurship (ENT300) Busines Plan : Sushi Bae Enterprise / Suria Atika Ahmad Asri - Ahmad Asri, Suria Atika (2019)
Sushi Bae Enterprise is a new modern restaurant specializing sushi meals, beverages and dessert. Within the last three months there has been significant increases in demand for these products especially when Sushi Bae Enterprise release new productline offered better boost ingredient concern for health and wellness. This can be explained to a large degree by the fact that up until recently Malaysian have had infected with Coronavirus. It has been only in the last few months that medical doctors have begun to diagnosis the virus correctly. What was once an unknown problem that affected so many people with no recourse has become a manageable ailment that is easily dealt with through modification of diets. This is very positive for both those people that are affected as well as restaurant such as Sushi Bae Enterprise that have specialness on healthy meals.